2000
DOI: 10.1034/j.1600-0420.2000.078004386.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler imaging of the ocular circulation in diabetic retinopathy

Abstract: ABSTRACT.Purpose: To measure blood flow velocity in the ophthalmic artery (OA) and central retinal artery (CRA) in patients with diabetic retinopathy. Subjects and Methods: 62 age-matched subjects divided into 3 groups: nondiabetic controls (nΩ17); diabetics with no clinical retinopathy or background changes (nΩ24); diabetics with either pre-proliferative or proliferative retinopathy (nΩ21). Colour Doppler imaging was performed on supine patients by one masked observer using the Acuson 128 machine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
4
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 21 publications
6
55
4
5
Order By: Relevance
“…Our finding of an increased resistivity index in the ophthalmic artery and central retinal vein is similar to that reported by MacKinnon et al [11]. The finding that the resistivity and pulsatile indices of the central retinal artery, posterior ciliary artery, and ophthalmic artery in patients with and without retinopathy are significantly greater than those of healthy individuals is also in agreement with certain other studies [6,[25][26][27].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our finding of an increased resistivity index in the ophthalmic artery and central retinal vein is similar to that reported by MacKinnon et al [11]. The finding that the resistivity and pulsatile indices of the central retinal artery, posterior ciliary artery, and ophthalmic artery in patients with and without retinopathy are significantly greater than those of healthy individuals is also in agreement with certain other studies [6,[25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, studies using color Doppler imaging reported a reduced blood flow velocity in patients with diabetes which appeared to become further reduced as retinopathy progressed [6,25]. Two other studies evaluated the blood flow velocities of the ophthalmic artery, central retinal artery, and posterior ciliary artery and found decreased PSV and EDV in the central retinal artery in patients with retinopathy [9,11]. Similar results were reported by Mendivil et al, who analyzed 25 type 1 and type 2 diabetes patients with proliferative retinopathy and 30 non-diabetic controls [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is an ultrasonographic method that has been employed for the evaluation of the circulatory status in much ocular pathology, but is most used for the investigation of the circulatory status in retinal vascular disorders and in glaucoma. [1][2][3] Ultrasound imaging (sonography) is accomplished with a pulse-echo technique. Pulses of ultrasound (generated by a transducer) are sent into the patient where they produce echoes at organ boundaries and within tissues.…”
Section: Imagingmentioning
confidence: 99%